29.4k views
5 votes
Need this ASAP please

Need this ASAP please-example-1
User Sidi Shah
by
4.6k points

1 Answer

1 vote

Answer:

C

Explanation:

Because if we multiply by 2 both member we have

(x-12)(x-4)= 0

A product has a result that is equal to iif at least one of its factor is equal to 0, so we can solve this two equations:

x-12 = 0

x = 12

x-4 = 0

x = 4

User Jsight
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.